If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -8q = 5 Solving 3p + -8q = 5 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '8q' to each side of the equation. 3p + -8q + 8q = 5 + 8q Combine like terms: -8q + 8q = 0 3p + 0 = 5 + 8q 3p = 5 + 8q Divide each side by '3'. p = 1.666666667 + 2.666666667q Simplifying p = 1.666666667 + 2.666666667q
| 9y=-7.5x+33 | | -3=10a-10 | | x+y+40=180 | | 5tanx+3=4 | | x+2/2=-4 | | -4(4-x)=3(x-6) | | 5p-9q=17 | | -7(-8)= | | 5x^2+36x+24=0 | | 4x+3y=9y-5x | | -4a+1=13 | | 340x+1070(-x+11)=9580 | | 30=2x+5x+2 | | 3y+3x+9x=180 | | TC=5+4Q+0.6Q^2 | | 2y=0+3 | | TC=100+4Q+0.4Q^3 | | 29=t+4 | | 5tanx+3=0 | | 8t-24=0 | | 2.7=13.5 | | y=6*-2+18 | | 4r^2=y | | 0=m-6 | | -17=8a+5 | | o=m-6 | | 6(6x+18)+4x=28 | | 2w+2(46-w)=46 | | 4x-9=o | | 2w+2(46-n)=46 | | .75X+2=4.666666 | | 7x-28+3x-18=6x-12 |